2017
DOI: 10.5194/amt-10-1831-2017
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution airborne imaging DOAS measurements of NO<sub>2</sub> above Bucharest during AROMAT

Abstract: Abstract. In this study we report on airborne imaging DOAS measurements of NO 2 from two flights performed in Bucharest during the AROMAT campaign (Airborne ROmanian Measurements of Aerosols and Trace gases) in September 2014. These measurements were performed with the Airborne imaging Differential Optical Absorption Spectroscopy (DOAS) instrument for Measurements of Atmospheric Pollution (AirMAP) and provide nearly gapless maps of column densities of NO 2 below the aircraft with a high spatial resolution of b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 54 publications
2
43
0
Order By: Relevance
“…Temperature and pressure profiles from the NAM-CMAQ in the troposphere and the Realtime Air Quality Modeling System (RAQMS; Pierce et al, 2009) up to 60 km are extracted and merged, and ozone profiles are extracted from the NAM-CMAQ analysis for the troposphere and OMI gridded monthly climatology in the stratosphere for May and June 2017. Noguchi et al (2014) evaluated the influence of surface anisotropy on NO 2 AMFs for geostationary-scale measurements using a 1 km MODIS BRDF product and found that not accounting for BRDF in the AMF calculation, especially in areas with high NO 2 near the surface, can lead to large errors. For this reason, this work uses the BRDF isometric, volumetric, and geometric kernels retrieved in band 3 by the MODIS MCD43A1 daily L3 500 m v006 product (Lucht et al, 2000;Schaaf and Wang, 2015).…”
Section: Slant-to-vertical Column Conversionmentioning
confidence: 99%
“…Temperature and pressure profiles from the NAM-CMAQ in the troposphere and the Realtime Air Quality Modeling System (RAQMS; Pierce et al, 2009) up to 60 km are extracted and merged, and ozone profiles are extracted from the NAM-CMAQ analysis for the troposphere and OMI gridded monthly climatology in the stratosphere for May and June 2017. Noguchi et al (2014) evaluated the influence of surface anisotropy on NO 2 AMFs for geostationary-scale measurements using a 1 km MODIS BRDF product and found that not accounting for BRDF in the AMF calculation, especially in areas with high NO 2 near the surface, can lead to large errors. For this reason, this work uses the BRDF isometric, volumetric, and geometric kernels retrieved in band 3 by the MODIS MCD43A1 daily L3 500 m v006 product (Lucht et al, 2000;Schaaf and Wang, 2015).…”
Section: Slant-to-vertical Column Conversionmentioning
confidence: 99%
“…NO x is involved in the formation of photochemical ozone and fine aerosol particles, with implications for both surface air quality and climate. Both short-and long-term enhanced NO 2 concentrations are associated with increased mortality (Hoek et al, 2013;Mills et al, 2015). NO x emissions can also lead to excess nitrogen deposition (Fowler et al, 2013;Nowlan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With this setup, 35 across-track pixels are measured simultaneously with an exposure time of 0.5 s, leading to a spatial resolution better than 50 m when the aircraft is flying at 1600 m altitude. For more detailed information on the instrument see Schönhardt et al (2015) and Meier et al (2017).…”
Section: Validationmentioning
confidence: 99%